2016
DOI: 10.1002/1873-3468.12220
|View full text |Cite
|
Sign up to set email alerts
|

PAUPAR lncRNA suppresses tumourigenesis by H3K4 demethylation in uveal melanoma

Abstract: Edited by Tamas DalmayUveal melanoma (UM) is the most common primary intraocular tumour in adults and has a high incidence. Nearly 50% of patients with UM develop metastases after diagnosis. Long noncoding RNAs (lncRNAs) are involved in both oncogenic and tumour suppression pathways. We show that lncRNA PAUPAR is present at low levels in UM tissues and cell lines and modulates the tumourigenesis of UM in vitro and in vivo. The ectopic expression of PAUPAR in UM cells revealed that PAUPAR acts as a necessary UM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Pauper was previously identified as a CNS-specific lncRNA expressed from the Pax6 locus that was able to bind multiple regulatory elements in cis and trans and linked to intraocular tumours (45,57). Using short hairpin RNA-mediated downregulation of Paupar, Vance et al (45) showed it could transcriptionally regulate Pax6 , whilst Pax6 knockdown did not affect Paupar levels, suggesting that the mechanism was not via a Pax6 autoregulatory affect.…”
Section: Discussionmentioning
confidence: 99%
“…Pauper was previously identified as a CNS-specific lncRNA expressed from the Pax6 locus that was able to bind multiple regulatory elements in cis and trans and linked to intraocular tumours (45,57). Using short hairpin RNA-mediated downregulation of Paupar, Vance et al (45) showed it could transcriptionally regulate Pax6 , whilst Pax6 knockdown did not affect Paupar levels, suggesting that the mechanism was not via a Pax6 autoregulatory affect.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al discovered that lncRNA PAUPAR acted as a necessary UM suppressor and could silence HES1 expression, which significantly reduced metastasis. Mechanistically, PAUPAR inhibits histone H3K4 methylation to modulate HES1 expression 37. Lei demonstrated that lncRNA MALAT1 was upregulated in the uveal melanoma tissues and cell lines.…”
Section: Epigenetic Mechanisms In Ummentioning
confidence: 99%
“…In addition, transcription factor HES1 is overexpressed in UM cell lines and is associated with its metastatic capacity. And one of the reasons of upregulated expression of HES1 in UM cells is H3K4 trimethylation of the HES1 promoter 37.…”
Section: Epigenetic Mechanisms In Ummentioning
confidence: 99%
“…The lncRNA PAX6 upstream antisense RNA (PAUPAR) was found in uveal melanoma tissues and uveal melanoma cell lines at low levels, suggesting that it might act as a tumor suppressor lncRNA [114]. Effectively it impacts tumorigenesis in vitro and in vivo by reducing tumor metastases significantly.…”
Section: Long Non-coding Rnas In Melanomamentioning
confidence: 99%
“…Effectively it impacts tumorigenesis in vitro and in vivo by reducing tumor metastases significantly. Further experiments showed that PAUPAR acts as a guide lncRNA by inducing the silencing of the transcription factor hairy and enhancer of split-1(HES1) by inhibiting histone H3K4 tri-methylation at the HES1 locus (Figure 1B and Table 1) [114]. …”
Section: Long Non-coding Rnas In Melanomamentioning
confidence: 99%